Is Neuronal Histamine Signaling Involved in Cancer Cachexia? Implications and Perspectives - Zwickl, Hannes; Zwickl-Traxler, Elisabeth; Pecherstorfer, Martin (Frontiers in Oncology, 2019)
In this paper, we present evidence in support of our hypothesis that the neuronal histaminergic system might be involved in cancer cachexia. To build our premise, we present the research and the reasonable inferences that can be drawn from it in a section-by-section approach starting from one of the key issues related to cachexia, increased resting energy expenditure (REE), and progressing to the other, anorexia. Based on an extensive survey of the literature and our own deliberations on the abovementioned topics, we investigate whether histamine signaling might be the mechanism used by a tumor to hijack the body’s thermogenic machinery. Our hypothesis in short: Hypothalamic histaminergic neurons are stimulated by inputs from the parasympathetic nervous system (PSNS), which senses tumor traits early in cancer development. Histamine release in the POA primarily activates brown adipose tissue (BAT), triggering a highly energy-demanding mechanism. Chronic activation of BAT, which, in this context, refers to intermittent and/or low-grade activation by the sympathetic nervous system, leads to browning of WAT and further enhances thermogenic potential. Aberrant histamine signaling not only triggers energy-consuming processes, but also anorexia. Moreover, since functions such as taste, smell, and sleep are governed by discrete structures of the brain, which are targeted by distinct histaminergic neuron populations; even relatively minor symptoms of cachexia, such as sleep disturbances and taste and smell distortions, also might be ascribed to aberrant histamine signaling. In late-stage cachexia, the sympathetic tone in skeletal muscle breaks down, which we hypothesize might be caused by a reduction in histamine signaling or by the interference of other cachexia-related mechanisms. Histamine signaling thus might delineate distinct stages of cachexia progression, with the early phase marked by a PSNS-mediated increase in histamine signaling, increased sympathetic tone and symptomatic adipose tissue depletion, and the late phase characterized by reduced histamine signaling, decreased sympathetic tone and symptomatic muscle wasting. Extrapolating from the current body of knowledge, we develop our hypothetical framework about the role of a distinct neuron population in the pathophysiology of cancer cachexia. Our hope is that presenting our ideas will spark discussion about the pathophysiology of cachexia.